CARDIORESPIRATORY DISFUNCTIONS IN PATIENTS WITH SUBCLINICAL HYPOTHYROIDISM (Fiep Bulletin - online, 2015)
The subclinical hypothyroidism is characterized by the increased serum value of thyrotropin (TSH), normal concentrations of triiodothyronine free (FT3) and serum free thyroxine (FT4).  The aim of the present study was to compare the level of physical condition of seven patients with seven healthy women, by the ergoespirometry.  The data had been compared through the test of Mann-Whitney U (p
Keywords: Subclinical Hypotyreoidism; Ergoespirometry; Cardio respiratory capacity.